Imbalance in the antioxidant defence system and pro-genotoxic status induced by high glucose concentrations: In vitro testing in human liver cells. (December 2020) - Acito, Mattia; Bartolini, Desirée; Ceccarini, Maria Rachele; Russo, Carla; Vannini, Samuele; Dominici, Luca; Codini, Michela; Villarini, Milena; Galli, Francesco; Beccari, Tommaso; Moretti, Massimo
Abstract: It has been hypothesized that high glucose concentrations might contribute to the overall intracellular oxidative stress either by the direct generation of reactive oxygen species (ROS) or by altering the redox balance. Moreover, it has also been suggested that high glucose concentration can increase the susceptibility of DNA to genotoxic effects of xenobiotics. The aim of this approach was to test high glucose concentrations for pro-genotoxicity in human liver cells by setting up an in vitro model for hyperglycaemia. The experimental design included performing of tests on both human HepG2 tumour cells and HepaRG immortalized cells. Increased cell susceptibility to genotoxic xenobiotics was tested by challenging cell cultures with 4-nitroquinoline- N -oxide (4NQO) and evaluating the extent of primary DNA damage by comet assay. Moreover, we evaluated the relationship between glucose concentration and intracellular ROS, as well as the effects of glucose concentration on the induction of Nrf2-dependent genes such as Glutathione S -transferases, Heme‑oxygenase-1, and Glutathione peroxidase-4. To investigate the involvement of ROS in the induced pro-genotoxic activity, parallel experimental sets were set up by considering co-treatment of cells with the model mutagen 4NQO and the antioxidant, glutathione precursor N -acetyl-L-cysteine. High glucose concentrations caused a significant increase in the levels of primary DNA damage, with a pro-genotoxic condition closely related to the concentration of glucose in the culture medium when cells were exposed to 4NQO. High glucose concentrations also stimulated the production of ROS and down-regulated genes involved in contrasting of the effects of oxidative stress. In conclusion, in the presence of high concentrations of glucose, the cells are in unfavourable conditions for the maintenance of genome integrity. Highlights: High glucose concentrations increase cell susceptibility to genotoxic xenobiotics. High glucose concentrations promote an increase of intracellular ROS. High glucose concentrations down regulate gene expression of genes protective in conditions of oxidative stress.